Pengaruh Klaim INA Cbg BPJS Rawat Inap Dan Rawat Jalan Terhadap Struktur Modal Rumah Sakit Advent Bandar Lampung - Hamidah Hamidah; Nur Salma; Novalita Novalita (CV. ULIL ALBAB CORP, 2024)
The purpose of this research was to know the effect of the impact of INA cbg bpjs claim and inpatient on capital structure bandar lampung adventist hospital. The data in this research is claims report data and capital structure data for 2019-2022. The method used is a descriptive method using secondary data. Based on the test results of this research, the influence of X1 and The F test results show that the Fcount value obtained is 12.551 with an Ftable value of 3.28 and a sig value. amounting to 0.000 < 0.05, then it can be concluded that inpatient and outpatient claims have an effect on capital structure, the results of the T test in this study, the calculated T value on the inpatient claim variable is 2.402 > 2.035 and the sig value is 0.022 < 0.05, so it can be The conclusion is that outpatient claims have a significant effect on capital structure, while the T-test results on the outpatient claims variable are 1.953<2.035 and the significance is 0.059>0.005, so it can be concluded that outpatient claims do not have a significant effect on capital structure. The results of the Linear Regression Analysis Test show the influence of inpatient and outpatient BPJS claims on capital structure 53,407 + 0.351X1+ 0.633X2